The Relationship Between Smartphone Usage Pattern and Cervical Proprioception in Adults with Text Neck Syndrome in Malaysia - Vinosh Kumar Purushothaman; Vinodhkumar Ramalingam; Ryan Wee Yao Xian; Sharmila Gopala Krishna Pillai; Mohammed Abdulrazzaq Jabbar; Yughdtheswari Muniandy; Arun Vijay Subbarayalu; Rajkumar Krishnan Vasanthi (Medsci Publications, 2023)
Background: Text neck syndrome can cause cervical degeneration in addition to other developmental, musculoskeletal, and social complications. The aim of the current study is to examine the association between smartphone usage patterns and demographics with cervical spine joint proprioception in adults with text neck syndrome (TNS). Methodology: A cross-sectional study design was chosen to investigate the association between sociodemographic and smartphone usage patterns with cervical joint proprioception. A validated smartphone usage pattern questionnaire was administered to 125 participants who used smartphones for more than three hours a day and suffered from TNS, and all samples underwent cervical proprioception testing. Data were analyzed using descriptive statistics, chi-square tests, and independent t-tests. Results: The result shows that there was a significant association between gender, education, BMI, phone usage hours and cervical proprioception (p<0.05). However, no significant association was found with smartphone usage pattern and cervical proprioception. Conclusions: It is concluded that smartphone use can negatively impact cervical proprioception. Smartphone users are advised to be aware of these potential health risks and take steps to reduce them to achieve better health and well-being.